(untitled) (LACCEI, 2024)
The adoption of Lean manufacturing strategy significantly boosts the performance of an industrial company, focusing on activities that add value, and seek to eliminate all waste or activity that does not add value to the customer. On the other hand, the Industry 4.0 model is considered a world-class paradigm that aims to empower people and optimize processes through various technologies arising from digitization. The combination of these models resulted in terms like "lean 4.0". However, there is no clear and detailed definition of the result of the integration of both paradigms. This work investigates the opportunities and strengths generated by the complementation of Lean management and Industry 4.0, and how the Industry 4.0 model can facilitate and strengthen the adoption of Lean methodology. The article addresses the importance of an innovation ecosystem for its diffusion in the productive framework, and the role of the University in the process of adopting new practices in companies. The new industrial model includes a complexity and depth that cannot be addressed by a single institution, the successful models in Europe and particularly Germany are supported by Innovation ecosystems. This article from an Industrial Engineering Research Group, based in the Faculty of Engineering of the National University of Lomas de Zamora presents a conceptual framework, and the work is being done with local SMEs. The paper presents three cases of firms that are optimizing production processes with the aid of Lean 4.0 strategy. The importance of an innovation ecosystem in the approach of the SMEs firms to the new paradigm is highlighted in the paper.